From Family to Police Force : Security and Belonging on a South Asian Border - Ibrahim, Farhana (Book collections on Project MUSE., 2021)
"Based on ethnographic research in the western Indian borderland region of Kutch, this book is an anthropological inquiry into forms of policing. It suggests that policing must be considered beyond its institutional and militarized sites, as an integral aspect of the family and the ways in which kinship is forged" --